2004
DOI: 10.1080/09500340408233616
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement purification through Zeno-like measurements

Abstract: We present a novel method for purifying quantum states, i.e. purification through Zeno-like measurements, and show an application to entanglement purijication. = 14)x (41 8 Q~' ( N ) , (2) Journal of Modern Optics

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Since an entangled state of system A+B is one of the pure states, there is a possibility that we apply the purification mechanism described above to distill the initial (generally mixed) state of A+B to a desired entangled state. This possibility has already been pointed out and it has been explicitly demonstrated that one of the Bell states |Ψ − of the two qubit systems A+B can actually be extracted if we repeatedly measure one and the same state of another qubit system X, the interactions of which are symmetrical with respect to A and B, resulting with the maximal yield [5,6]. One of the limitations of this model is that the entanglement can be established only when the two systems A and B locally interact with the same system X at the same time and therefore it does not seem to allow to establish an entanglement between two systems that are spatially separated.…”
Section: Entanglement Distillation In a Two-qubit System A+b By mentioning
confidence: 92%
See 4 more Smart Citations
“…Since an entangled state of system A+B is one of the pure states, there is a possibility that we apply the purification mechanism described above to distill the initial (generally mixed) state of A+B to a desired entangled state. This possibility has already been pointed out and it has been explicitly demonstrated that one of the Bell states |Ψ − of the two qubit systems A+B can actually be extracted if we repeatedly measure one and the same state of another qubit system X, the interactions of which are symmetrical with respect to A and B, resulting with the maximal yield [5,6]. One of the limitations of this model is that the entanglement can be established only when the two systems A and B locally interact with the same system X at the same time and therefore it does not seem to allow to establish an entanglement between two systems that are spatially separated.…”
Section: Entanglement Distillation In a Two-qubit System A+b By mentioning
confidence: 92%
“…The eigenvalue λ n is complex valued in general, but its absolute value is bounded [5] 0 ≤ |λ n | ≤ 1. (2.8) This reflects the unitarity of the time evolution operator e −iHτ .…”
Section: Purification Via Repeated Measurementsmentioning
confidence: 99%
See 3 more Smart Citations